Víboras y partos violentos en Lope de Vega - Sánchez Jiménez, Antonio (Avisos de Viena, 2021)
One of the most widespread birth images in Golden Age literature is that of the horrifying birth of the viper. This motif, extensively recounted by natural philosophers of Antiquity and documented in various sources, symbolizes violent childbirth. This article examines the prevalence and significance of this motif in the works of Lope de Vega and Calderón, comparing its usage and implications across their respective oeuvres. Through an analysis of textual occurrences in TESO's corpus, this study sheds light on the multifaceted symbolism associated with the viper's birth, ranging from themes of betrayal to self-destruction.